Oxytocin and mutual communication in mother-infant bonding - Nagasawa, Miho; Okabe, Shota; Mogi, Kazutaka; Kikusui, Takefumi (Frontiers in Human Neuroscience, 2012)
Mother-infant bonding is universal to all mammalian species. In this review, we describe the manner in which reciprocal communication between the mother and infant leads to mother-infant bonding in rodents. In rats and mice, mother-infant bond formation is reinforced by various social stimuli, such as tactile stimuli and ultrasonic vocalizations from the pups to the mother, and feeding and tactile stimulation from the mother to the pups. Some evidence suggests that mother and infant can develop a cross-modal sensory recognition of their counterpart during this bonding process. Neurochemically, oxytocin in the neural system plays a pivotal role in each side of the mother-infant bonding process, although the mechanisms underlying bond formation in the brains of infants has not yet been clarified. Impairment of mother-infant bonding, that is, deprivation of social stimuli from the mother, strongly influences offspring sociality, including maternal behavior toward their own offspring in their adulthood, implying a “non-genomic transmission of maternal environment,” even in rodents. The comparative understanding of cognitive functions between mother and infants, and the biological mechanisms involved in mother-infant bonding may help us understand psychiatric disorders associated with mother-infant relationships.